Adherence to oral chemotherapy: Evidence from a randomised clinical trial. (2nd October 2020) - Ghiggia, Ada; Bianco, Alessandra; Castelli, Lorys; Baratta, Francesca; Birocco, Nadia; Scaldaferri, Matilde; Milla, Paola; Tesio, Valentina; Rosso, Stefano; Torta, Riccardo; Brusa, Paola; Cattel, Francesco
Abstract: Objective: To evaluate the efficacy of a reinforcement message (RM) administered by a hospital pharmacist on adherence, through a randomised study involving patients undergoing oral chemotherapy from which an objective outcome measure and patients' subjective opinions were collected. A secondary aim was to detect which psychological or clinical factors influence adherence. Methods: Forty patients were enrolled and randomised to an experimental group (EG) or a control group (CG). The EG received a 10‐minute RM provided by a hospital pharmacist with a doctor and a nurse. The CG received the standard of care. To measure adherence, plasma drug concentration and subjective evaluation were taken during the visits, in addition to a psychological assessment (coping strategies, psychological distress and personality traits). Results: The EG reported higher drug levels and a statistically significant higher mean score on the subjective evaluation. A linear regression model highlighted statistically significant differences in the plasma drug concentration, after considering toxicity and dose reduction and controlling for the Reward Dependence Scale of the Temperament and Character Inventory between the EG and the CG. Conclusion: Adequate information and education on the therapy, using an RM strategy provided by a hospital pharmacist, seems to positively influence adherence to the treatment.